2020
DOI: 10.1071/rd20107
|View full text |Cite
|
Sign up to set email alerts
|

Calorie restriction during gestation affects ovarian reserve in offspring in the mouse

Abstract: The aim of this study was to investigate the effect of calorie restriction (CR) during pregnancy in mice on metabolism and ovarian function in the offspring. Pregnant female mice were divided into two groups, a control group and a CR group (n=7 in each). Mice in the CR group were fed 50% of the amount consumed by control females from Day 10 of gestation until delivery. After weaning, the offspring received diet ad libitum until 3 months of age, when ovaries were collected. Ovaries were serially cut and every s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…We found that the level of dietary protein alters the mRNA transcripts of HPG-axis genes, particularly in the ovaries of early life broiler chicks, potentially affecting future folliculogenesis. Our results are consistent with those of other studies and suggest that maternal or neonatal imbalanced nutritional intake influences folliculogenesis and reproduction during the pubertal and prepubertal stages in animals, including BB hens [10,44,45].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the level of dietary protein alters the mRNA transcripts of HPG-axis genes, particularly in the ovaries of early life broiler chicks, potentially affecting future folliculogenesis. Our results are consistent with those of other studies and suggest that maternal or neonatal imbalanced nutritional intake influences folliculogenesis and reproduction during the pubertal and prepubertal stages in animals, including BB hens [10,44,45].…”
Section: Discussionsupporting
confidence: 93%
“…Gestational dietary restriction also affects ovarian development in rodents. [14][15][16][17][18] These studies have included reduced total diet, calories or protein and imposed various degrees of nutritional restrictions, and all revealed that maternal undernourishment is deleterious to the fertility of female offspring. It is thought that protein restriction during pregnancy has a more profound impact on foetal development since deficiency of amino acids demands more changes in maternal metabolism.…”
Section: Undernutrition and Human Reproduction Prenatal/maternal Unde...mentioning
confidence: 99%
“…These findings clearly demonstrated the negative impact of maternal undernutrition on male reproduction. Gestational dietary restriction also affects ovarian development in rodents 14–18 . These studies have included reduced total diet, calories or protein and imposed various degrees of nutritional restrictions, and all revealed that maternal undernourishment is deleterious to the fertility of female offspring.…”
Section: Undernutrition and Human Reproductionmentioning
confidence: 99%